A content analysis on diversity and persons with disabilities in CSR-awarded companies in Malaysia / Anisa Safiah Maznorbalia, Zurina Ismail and Zuhal Hussein - Maznorbalia, Anisa Safiah; Ismail, Zurina; Hussein, Zuhal (Universiti Teknologi MARA, 2021)
Diversity is a concept that includes individuals from different categories and centrally aims at creating an inclusive community that values and utilizes all members' talents. Diversity in the workplace has long been recognized as beneficial to the organization's whole performance. Apart from creating an inclusive environment, having a diverse workforce means having a different set of skills, ideas, attitudes, knowledge, and thus giving a higher chance for an organization to be in a competitive advantage. Despite all the advantages, persons with disabilities (PWD) as one of the diversity categories have always been excluded from entering the labor market. Therefore, the aim of this study is to do a systematic empirical investigation on PWD's employment within the organizations by examining the annual report of the CSR-awarded organizations in Malaysia to evaluate how far these organizations are reporting their diverse workforce and accepting the inclusion of PWD in the companies. The quantitative content analysis method was used in this study. 14 published annual reports of CSR-awarded companies from the year 2019 were selected as a sample. Employees with PWD were recorded by two companies, with percentages of 0.18 percent and 0.05 percent, respectively. The result shows the employment data on disability among companies that have won CSR awards in Malaysia are scarce. The companies tend to place more emphasis on other diversity categories, especially on gender and age group. It is suggested for future research to explore the employment of PWD from the perspective of corporate social responsibility since anything related to PWD should be addressed through social imperatives.